Exploring Determinants of English Paragraph Writing Difficulties among EFL High School Learners: A Study from Cambodia - Mariya, Seth; Chenda, Soeurn; Cheu, Kouy; Lida, Sorl; Sovann, Ly (Institut Agama Islam Negeri Kudus, 2025)
The primary purpose of this study was to identify factors affecting the English paragraph writing of 12th-grade students. The study was conducted at a high school in Thmor Korl, Cambodia, with special reference to grade 12. The issue was addressed using a qualitative research strategy. Two English language teachers and 84 students were selected for this study. Questionnaires were used in the study to survey factors affecting students' paragraph writing and examine ways to improve their skills. The data was analyzed quantitatively. The study's results illustrated that students lack of grammar, basic strategies for writing paragraphs, lack of practice, vocabulary, structure, paragraph organization, poor reading, motivation, time constraints, and teacher-related factors such as teachers’ ways of giving feedback and teaching strategies. Therefore, students should be given chances to practice paragraph writing skills sufficiently to become effective paragraph writers, since paragraph writing requires practice and feedback. Beyond these findings, future researchers should study paragraph analysis and action research for more valuable results.